Real Wages, Inflation and Labor Productivity in Turkey - Bakır, Hasan; Eryılmaz, Filiz (My University, 2018)
Nowadays, where being competitive is considered equal to productivity, productivity and factors affecting productivity constitute a popular discussion area. Hence, as the relevant literature is reviewed, it was observed that attention focuses on labor productivity and on the relationship between wages and inflation, which are considered as the factors that affect the productivity. In this study, while cointegration test of Johansen (1988) and Johansen/Juselius (1990) was used to investigate whether there is a long-term relationship or not between real wages, productivity and inflation in Turkey during the period 1988-2012, the direction of this relationship was examined via the Vector Error Correction Model (VECM). The results demonstrated a long-term relationship between all three variables and the direction of this relationship in the long-term was determined as, from productivity and inflation towards the real wages. Moreover, in short-term, a causality relationship was determined both from inflation to real wages and from inflation to productivity. On the other hand, the identification of the negative effect of the crises on productivity is one of the important results reached by this study.

Rekabetçi olmanın verimlilikle eş tutulduğu günümüzde çağda verimlilik ve verimliliği etkileyen faktörler popüler bir tartışma alanını oluşturmaktadır. Nitekim ilgili literatür incelendiğinde dikkatlerin emek verimliliği ve verimliliği etkileyecek faktörler olarak görülen ücretler ve enflasyon arasındaki ilişkide toplandığı gözlenmiştir. Bu çalışmada 1988-2012 döneminde Türkiye’de reel ücretler, verimlilik ve enflasyon arasında uzun dönemli ilişki olup olmadığı kointegrasyon analizi araştırılırken söz konusu ilişkinin yönü Vektör Hata Düzeltme Modeli (VECM) ile incelenmiştir. Çalışma sonucunda her üç değişken arasında uzun dönemli ilişki olduğu görülmüş ve uzun dönemde söz konusu ilişkinin yönünün verimlilik ve enflasyondan reel ücretlere doğru olduğu tespit edilmiştir. Yine kısa dönemde de hem enflasyondan reel ücretlere hem de enflasyondan verimliliğe doğru bir nedensellik ilişkisi olduğu tespit edilmiştir. Öte yandan Türkiye’de yaşanan krizlerin verimliliği azaltıcı etkisinin belirlenmesi de bu bağlamda çalışmanın ulaştığı önemli sonuçlardandır.
Reel Ücretler, Enflasyon ve İşgücü Verimliliği: Türkiye Bağlamında Bir Değerlendirme
Keywords: Emek Verimliliği; Reel Ücretler; Enflasyon; Kointegrasyon Analizi; VECM; Labor Productivity; Real Wages; Inflation; Cointegration Analysis